ANALISIS ASPEK PENGELOLAAN KOLABORATIF DI TAMAN NASIONAL LAUT KEPULAUAN SERIBU (TNKpS) - Eka Dana Prabowo; Harnios Arief; Tutut Sunarminto (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
TNKpS gap management for achieving management goals can be emerge when the goals are not able to compensated with the resources owned. So alternative management that can be done was colaborated with other stakeholders. One of the basic collaboration is to know the goals detail and resources that belonging to the stakeholders. The purpose of this research is to analyze the goals and resources belonging to the stakeholders. Research carried out in all SPTN TNKpS, at November and December 2014 and January and February 2015. The data that collected consist of supporting data in the form of management document, report activities, and literature. While the main data consist of RPTN TNKpS documents, the perception score of management goals (economic, social, and ecology) and stakeholders resources (human, financial, physical, DIT) with functionality, importance, availability, and tangibility attributes. The stakeholders with ecological goals like BTNKpS, NGOs, and local government while the community, universities, and the private sector more in neutral role. The social goals done by local government with assessment score of 6,15 (appropriate category), also by BTNKpS and NGOs. While the economic goals done by private sector (5,97, appropriate category), and community (5,69 (appropriate category). The resources aspect, the quality of human resources TNKpS, local government, private sector, and NGOs is good enough, but less in the term of number. The financial aspect quite a lot in the private sector and NGO as well as more adaptive. The physical aspects of private sector and local government quite a lot, while the community and the other institutions have less. SDIT aspects that owned by community are very much, but not in systematic and structured form. As a whole the purpose and resources which is owned by the stakeholders had been suitable and sufficient to cover up the gap management. Keyword: collaboratif management, gap, goals and resources, stakeholders, TNKpS